KEKUATAN MENGIKAT PUTUSAN AJUDIKASI BAWASLU DALAM SENGKETA PROSES PEMILU 2019 - Ahmad Rizqi Robbani Kaban; Rasji . (Jurnal Hukum Adigama, 2018)
The law governing general elections (elections) held every 5 years always changes. The latest is Law No.7 of 2017 (Elections Law) which accommodates 2019 Elections. In the Elections law law, the authority to resolve electoral disputes is regulated as one of the tasks of the Election Supervisory Body (Bawaslu). Bawaslu is given the authority to examine and decide on settlement of disputes through mediation if no agreement is reached then proceed to adjudication. Through this adjudication the problems occur, in the Election Law it is stated that the Bawaslu decision is final and binding. In fact, there is a decision on Bawaslu's adjudication which is not respected by the KPU. In the Election Law, the KPU is required to follow up on the decision no later than 3 (days) since the verdict was read. Instead of following up on the verdict, the KPU instead postponed following up on the verdict. Eventhough, the Election Law does not regulate the KPU's authority to delay, the KPU can only accept or reject it by making legal efforts to the Administrative Courts. So seeing the problem and being regulated by the Election Law, it is clear that the power of the Bawaslu adjudication decision is not final and binding. The Election Law must be corrected by giving firmness to the strength of the Bawaslu adjudication verdict whether it is final and binding or not.